Local Religious Traditions and Community Participation in Islamic Social Finance in Madura - Fahrurrozi Fahrurrozi; Farid Firmansyah; Wasilul Chair (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the role of local religious traditions in supporting Islamic social finance practices in Madura, Indonesia, with community participation as a mediating variable. It addresses the limited quantitative evidence on the socio-cultural foundations of Islamic social finance. Design/methodology/approach – A post-positivist quantitative approach was employed using quantitised interview data from 250 active or former koloman participants across four districts in Madura. Data were coded into three constructs—Local Religious Traditions (LRT), Community Participation (CP), and Islamic Social Finance Practices (ISF)—and analysed using partial least squares structural equation modelling (PLS-SEM). Findings/Results – Local religious traditions positively influence community participation and Islamic social finance practices, while community participation also has a significant positive effect on Islamic social finance practices. Furthermore, community participation partially mediates the relationship between local religious traditions and Islamic social finance practices. These findings indicate that koloman serves as an important socio-religious institution that strengthens collective fundraising, social assistance, and community-based productive support. Originality/Value – This study contributes to the Islamic social finance literature by integrating local religious traditions, community participation, and Islamic social finance practices into a single quantitative model. It demonstrates that koloman functions as a form of spiritual social capital that sustains Islamic social finance beyond formal institutional mechanisms.